EFEKTIVITAS VIDEO PEMBELAJARAN TERHADAP HASIL BELAJAR IPA DI MASA PANDEMI COVID 19 PADA SISWA KELAS IV SD INPRES LANRAKI I KOTA MAKASSAR - Annisa Imaniah, Andi Nurul; Hamid, Sundari; St. Muriati (Fakultas Keguruan dan Ilmu Pendidikan, 2021)
This research was conducted with the aim of knowing the effectiveness of the instructional videos on the science learning outcomes during the covid-19 of fourth grade students of SD Inpres Lanraki 1 Makassar. This type of research is an experimental study with a Pre-Experimental One Group Pretest-Posttest research design. The population was all students of SD Inpres Lanraki 1 Makassar. The sample of this research was taken using cluster sampling technique, namely 25 of the fourth-grade students. The data collection technique of the study was the test and documentation techniques which were analysed using paired t-test using SPSS. The research data shows that t count > t table is 14.849> 1.710, consequently, H1 is accepted and H0 is rejected. Thus, it can be concluded that the instructional video is effective on students' science learning outcomes.